До характеристики принципів застосування стягнень за порушення трудової дисципліни - Теліженко, О. С.; Telizhenko, O. S. (Науковий вісник публічного та приватного права. - 2023. - Вип. 6. - С. 63-68, 2023)
У статті, спираючись на аналіз наукових поглядів вчених, запропоновано авторське визначення поняття принципів застосування стягнень за порушення трудової дисципліни. Акцентовано увагу на тому, що на сьогоднішній день в науковій літературі відсутній єдиний підхід щодо розуміння переліку відповідних принципів, а відтак сформовано авторське бачення щодо кола та змісту останніх. Наголошено, що окреслені у статті принципи не віднайшли свого законодавчого закріплення, а відтак ця прогалина має бути усунена у майбутньому Трудовому кодексі України, прийняття якого є актуальним. Зроблено висновок, що принципи в силу внутрішніх властивостей обумовлюють характер і сутність стягнень за порушення трудової дисципліни та механізм їх застосування. Саме вихідні, основоположні засади формують собою соціально-ідеологічну конструкцію стягнень, а також визначають їх гуманістичний вектор, який відповідає правовому, демократичному статусу держави.

The relevance of the article lies in the fact that the application of disciplinary sanctions for violation of labor discipline is a complex process in its essence, content and purpose, and therefore such a process should be based on a system of starting points, initial ideas, which are commonly called principles in the scientific literature. The study of the latter has important theoretical and practical significance, since the principles form not only the ideological basis of this institute, they directly affect its further development and effective functioning. In addition, the principles themselves provide the conditions under which sanctions will be applied in such a way as to ensure an adequate level of compliance with the principles of legality and justice in the field of labor in general. The purpose of the article is: to establish a circle and to provide a description of the key principles of the application of fines for violation of labor discipline. In the article, based on the analysis of the scientific views of scientists, the author's definition of the concept of the principles of applying sanctions for violation of labor discipline is proposed. Attention is focused on the fact that there is currently no unified approach to the list of relevant principles in the scientific literature, and therefore the author's vision regarding the scope and content of the latter is formed. It is emphasized that the principles outlined in the article have not found their legislative consolidation, and therefore this gap should be eliminated in the future Labor Code of Ukraine, the adoption of which is urgent. It was concluded that the principles, due to their internal properties, determine the nature and essence of sanctions for violation of labor discipline and the mechanism of their application. It is the initial, fundamental principles that form the socio-ideological construction of sanctions, and also determine their humanistic vector, which corresponds to the legal, democratic status of the state. However, as a shortcoming it is worth noting the fact that the principles outlined by us have not found their legislative consolidation, and therefore this gap should be eliminated in the future Labor Code of Ukraine, the adoption of which is relevant for the modern Ukrainian state.

В статье, опираясь на анализ научных взглядов ученых, предложено авторское определение понятия принципов применения взысканий за нарушение трудовой дисциплины. Акцентировано внимание на том, что на сегодняшний день в научной литературе отсутствует единый подход к пониманию перечня соответствующих принципов, а затем сформировано авторское видение круга и содержания последних. Отмечено, что очерченные в статье принципы не нашли своего законодательного закрепления, поэтому этот пробел должен быть устранен в будущем Трудовом кодексе Украины, принятие которого является актуальным. Сделано заключение, что принципы в силу внутренних свойств обусловливают характер и сущность взысканий за нарушение трудовой дисциплины и механизм их применения. Именно исходные, основополагающие устои формируют собой социально-идеологическую конструкцию взысканий, а также определяют их гуманистический вектор, отвечающий правовому, демократическому статусу государства.
To characterize the principles of applying sanctions for violation of labor discipline
Keywords: принципи; принципи права; стягнення; правопорушення; трудова дисципліна; трудове законодавство; principles; principles of law; recovery; offense; labor discipline; labor legislation; принципы; принципы права; взыскания; правонарушения; трудовая дисциплина; трудовое законодательство